TRPV1 activation and internalization is part of the LPS-induced inflammation in human iPSC-derived cardiomyocytes - Sattler, Katherine; El-Battrawy, Ibrahim; Cyganek, Lukas; Lang, Siegfried; Lan, Huan; Li, Xin; Zhao, Zhihan; Utikal, Jochen; Wieland, Thomas; Borggrefe, Martin; Zhou, Xiao-Bo; Akın, Ibrahim (Scientific reports, 2021)
The non-selective cation channel transient receptor potential vanilloid 1 (TRPV1) is expressed throughout the cardiovascular system. Recent evidence shows a role for TRPV1 in inflammatory processes. The role of TRPV1 for myocardial inflammation has not been established yet. Human induced pluripotent stem cell (iPSC)-derived cardiomyocytes (hiPSC-CM) from 4 healthy donors were incubated with lipopolysaccharides (LPS, 6 h), TRPV1 agonist capsaicin (CAP, 20 min) or the antagonist capsazepine (CPZ, 20 min). TRPV1 expression was studied by PCR and western blotting. TRPV1 internalization was analyzed by immunofluorescence. Interleukin-6 (IL-6) secretion and phosphorylation of JNK, p38 and ERK were determined by ELISA. TRPV1-associated ion channel current was measured by patch clamp. TRPV1-mRNA and -protein were expressed in hiPSC-CM. TRPV1 was localized in the plasma membrane. LPS significantly increased secretion of IL-6 by 2.3-fold, which was prevented by pre-incubation with CPZ. LPS induced TRPV1 internalization. Phosphorylation levels of ERK, p38 or JNK were not altered by TRPV1 stimulation or inhibition. LPS and IL-6 significantly lowered TRPV1-mediated ion channel current. TRPV1 mediates the LPS-induced inflammation in cardiomyocytes, associated with changes of cellular electrophysiology. LPS-induced inflammation results in TRPV1 internalization. Further studies have to examine the underlying pathways and the clinical relevance of these findings.
Published: 19 July 2021
Gesehen am 31.05.2022